2014
DOI: 10.1016/s0016-5085(14)60585-0
|View full text |Cite
|
Sign up to set email alerts
|

943 MicroRNA 135a Suppresses Lymph Node Metastasis Through Down-Regulation of ROCK1 in Early Gastric Cancer

Abstract: MicroRNAs (miRNAs) play a critical role in gastric cancer progression and metastasis. This study investigated the role of miRNA-135a in early gastric cancer (EGC) including lymph node (LN) metastasis. We examined the correlation between miRNA-135a expression and clinical outcomes in 59 patients who underwent surgery for EGC. Using gastric cancer cell lines, we performed functional and target gene analyses. miRNA-135a expression was down-regulated in 33.9% of patients. These patients showed a significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…ROCK1, a member of the Rho‐associated serine/threonine kinase family, could facilitate the actin cytoskeleton reorganization during motion . It was confirmed to be upregulated in various cancers, such as gastric cancer, osteosarcoma, and prostate cancer . ROCK1 was considered as an oncogene because it was an crucial element in promoting migration, invasion, and metastasis of cancer cells .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROCK1, a member of the Rho‐associated serine/threonine kinase family, could facilitate the actin cytoskeleton reorganization during motion . It was confirmed to be upregulated in various cancers, such as gastric cancer, osteosarcoma, and prostate cancer . ROCK1 was considered as an oncogene because it was an crucial element in promoting migration, invasion, and metastasis of cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…**P < 0.01 when compared with NC-1 group or NC-2 group, respectively metastasis of cancer cells. 25 In Vennin et al 28 research, one of their important discoveries was that short-term targeted inhibition of ROCK1 could improve the efficacy of chemotherapy and also could destroy collective movement as well as impaired metastasis of pancreatic cancer cells, which is an major breakthrough in the clinical treatment of pancreatic cancer, even other cancers. Wu et al 29 suggested that the expression level of ROCK1 was closely associated with lymph node metastasis degree and tumor node metastasis (TNM) stage of gastric cancer, which could be used as a biological marker to evaluate malignancy degree of gastric cancer and also could be used as a predictor of gastric cancer occurrence, development, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROCK1 is a member of the Rho-associated serine/ threonine kinase family and play an important role in cell movement through reorganization of actin cytoskeleton [34]. It has been reported that ROCK1 is overexpressed in different cancers including prostate cancer [35], osteosarcoma [36], and gastric cancer [37]. ROCK1 gene is implicated in metastasis, invasion, and migration of cancer cells and could be considered as an oncogene [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ROCK1 is overexpressed in different cancers including prostate cancer [35], osteosarcoma [36], and gastric cancer [37]. ROCK1 gene is implicated in metastasis, invasion, and migration of cancer cells and could be considered as an oncogene [37]. Recent researches reported that the upregulation of ROCK1 is associated with poor survival in various cancers [38,39].…”
Section: Discussionmentioning
confidence: 99%